Testing the effects of a preceding self-control task on decision-making in soccer refereeing - Englert, Christoph; Dziuba, Anna; Schweizer, Geoffrey (Frontiers in neuroscience, 2021)
The present study tested the assumption that the momentary level of self-control strength affects the accuracy rates in a sports-related judgement and decision-making task. A total of N = 27 participants rated the veracity of 28 video-taped statements of soccer players who were interviewed by a non-visible referee after a critical game-related situation. In half of the videos, the players were lying and in the other half they were telling the truth. Participants were tested twice: once with temporarily depleted self-control strength and once with temporarily available self-control strength (order counterbalanced; measurements separated by exactly seven days). Self-control strength was experimentally manipulated with the Stroop task. In line with two-process models of information processing, we hypothesized that under ego depletion, information is processed in a rather heuristic manner, leading to lower accuracy rates. Contrary to our expectations, the level of temporarily available self-control strength did not have an effect on accuracy rates. Limitations and implications for future research endeavors are discussed.